1989
DOI: 10.1002/nau.1930080604
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods for quantification of urinary leakage in incontinent women

Abstract: To evaluate different methods for assessment of diagnosis and severity of urinary incontinence, 72 women underwent two consecutive 24 hours pad tests, a 1 hour pad test, a stress test, urodynamic examination, and a voiding-cysto-urethrography. The results were analysed and related to clinical findings.The 24 hours pad test revealed a good patient compliance, was as informative as to grade of incontinence as a 48 hours test, was reliable for all grades and types of incontinence, and correlated to clinical findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 4 publications
2
40
0
3
Order By: Relevance
“…19,32,43,52,80,[97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] The lead authors of these studies were contacted by letter and asked to provide further information. Four authors responded with all of the requested data.…”
Section: Results Of Contacting Authorsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,32,43,52,80,[97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] The lead authors of these studies were contacted by letter and asked to provide further information. Four authors responded with all of the requested data.…”
Section: Results Of Contacting Authorsmentioning
confidence: 99%
“…180 One paper assigned patients to three severity groups according to their self-reported urine loss and found significant differences in mean urinary loss between the three groups as measured by the 48-hour pad test. 112 Two papers studied the 24-hour pad test: one study 115 comparing the mean pad weight gain between self-reported incontinent and continent patient groups found no significant differences between the two groups. The other, 112 however, found significant differences in mean pad weight gain between three groups of patients grouped according to the self-perceived severity of their symptoms.…”
Section: Pad Test Compared With Clinical Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies regarding the reproducibility of the 24 and 48-hour pad tests have been conducted, the categories of mild, moderate and severe leakage have not been de®ned for these tests. The de®ni-tion of`continent' on the 24-hour pad test (5.5-8g or less of¯uid 13,14 ) should perhaps be further veri®ed, in nonovulatory postmenopausal women. In the current era of evidence based medicine, a robust outcome measure with adequate statistical and clinical repeatability is required, so that we may accurately determine whether our treatments for incontinence are effective.…”
Section: Discussionmentioning
confidence: 99%
“…While a 24-hour test is the most accurate, practical limitations most often mean that a one-hour test is the one used. 21,24 The interpretation of a one-hour test is: 0 to 1 g = normal/dry; 2 to 50 g = mild leakage; >50 grams = significant leakage.Laboratory investigations are particularly important when renal failure, polyuria or diabetes is suspected. The key tests to order are blood urea nitrogen, creatinine and glucose.…”
mentioning
confidence: 99%